2018
DOI: 10.1177/0011128718787154
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Association Between Massage Parlors and Neighborhood Crime

Abstract: Although massage parlors have been associated with illicit activities including prostitution, less is known about their association with neighborhood crime. Employing the Computer Automated Dispatch/Record Management System (CAD/RMS), online user review, licensing, Census, and zoning data, we examine the impact of massage parlors on crime in their surrounding neighborhoods. Using spatial autoregressive models, our results indicate the total number of massage parlors was associated with increased social disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…A larger city-level police force also did not prevent the local likelihood of IMBs, although the role of police presence may depend on how police are deployed rather than the number of police officers (Nagin et al, 2015). Furthermore, a positive association between violent crime arrest rates and the placement of IMBs was expected considering the evidence on the variety of violent crimes occurring in IMBs (Dank et al, 2014; Polaris, 2018) and the previously-reported association between the presence of IMBs and an increase in local crime and disorder (Huff et al, 2019). However, the odds for census tracts to have IMBs were higher in cities with lower violent crime rates, perhaps because violent crimes are more often recorded in disadvantaged areas while commercial sex venues are moving toward more advantaged and under-policed areas where buyer demand is anticipated to be higher (Chin et al, 2023; Murphy & Venkatesh, 2006).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A larger city-level police force also did not prevent the local likelihood of IMBs, although the role of police presence may depend on how police are deployed rather than the number of police officers (Nagin et al, 2015). Furthermore, a positive association between violent crime arrest rates and the placement of IMBs was expected considering the evidence on the variety of violent crimes occurring in IMBs (Dank et al, 2014; Polaris, 2018) and the previously-reported association between the presence of IMBs and an increase in local crime and disorder (Huff et al, 2019). However, the odds for census tracts to have IMBs were higher in cities with lower violent crime rates, perhaps because violent crimes are more often recorded in disadvantaged areas while commercial sex venues are moving toward more advantaged and under-policed areas where buyer demand is anticipated to be higher (Chin et al, 2023; Murphy & Venkatesh, 2006).…”
Section: Discussionmentioning
confidence: 85%
“…Similar to prior research on the locations of illicit massage businesses (Chin et al, 2023; Crotty & Bouché, 2018; Huff et al, 2019), information about the specific locations of IMBs was extracted from a popular, publicly-accessible, and comprehensive national reviewboard. 1 Customers of commercial sex (“Johns”) use this reviewboard to search by state and city for IMBs in their area and leave reviews with graphic details about the sexual services received and other details about the costs, the venue, judgments about the appearance and perceived age and racial and ethnic backgrounds of IMB staff.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation